Inhalational drug delivery from seven different spacer devices. Issue 8 (August 1996) - Barry, P. W.; O'Callaghan, C.
Abstract : BACKGROUND: A study was performed to determine in vitro the difference in drug output of seven currently available spacer devices when used with different inhaled medications. METHODS: A glass multistage liquid impinger (MSLI) was used to determine the amount of disodium cromoglycate (DSCG, 5 mg), salbutamol (100 micrograms), or budesonide (200 micrograms) obtained in various particle size ranges from metered dose inhalers (MDIs) actuated directly into the MSLI or via one of seven different spacer devices; the Fisonair, Nebuhaler, Volumatic, Inspirease, Aerochamber, Aerosol Cloud Enhancer, and Dynahaler. RESULTS: In particles smaller than 5 microns in diameter the dose of DSCG recovered from the Fisonair and Nebuhaler was 118% and 124%, respectively, of that recovered using the MDI alone. The dose recovered from the smaller volume spacers was 90% (Inspirease), 36% (Aerochamber), 33% (Aerosol Cloud Enhancer), and 21% (Dynahaler) of that from the MDI alone. The Volumatic increased the amount of salbutamol in particles smaller than 5 microns to 117% of that from the MDI, and the Inspirease and Aerochamber spacers decreased it by nearly 50%. The amount of budesonide in small particles recovered after use of the Nebuhaler, Inspirease, and the Aerochamber was 92%, 101%, and 78%, respectively, of that from the MDI alone. CONCLUSIONS: Under the test conditions used, large volume spacers such as the Fisonair, Nebuhaler, and Volumatic delivered significantly more DSCG and salbutamol than the smaller spacers tested. The differences between spacers were less for budesonide than the other medications studied. This study shows that there are significant differences in the amount of drug available for inhalation when different spacers are used as inhalational aids with different drugs. Spacer devices need to be fully evaluated for each drug prescribed for them.